Error Analysis: Past, Present, and Future. (February 2017) - McCloskey, George
This commentary will take an historical perspective on the Kaufman Test of Educational Achievement (KTEA) error analysis, discussing where it started, where it is today, and where it may be headed in the future. In addition, the commentary will compare and contrast the KTEA error analysis procedures that are rooted in psychometric methodology and the process approach to error analysis which is derived primarily from cognitive neuropsychology.